1984
DOI: 10.1523/jneurosci.04-06-01618.1984
|View full text |Cite
|
Sign up to set email alerts
|

Calcium/calmodulin-dependent protein phosphorylation in the nervous system of Aplysia

Abstract: An afterdischarge in the bag cell neurons of Aplysia was previously shown to be associated with calcium entry into these cells and with changes in the phosphorylation state of at least two bag cell proteins (BC-I and BC-II). We have now investigated the role of calcium plus calmodulin (Cal CaM) in the control of phosphorylation of Aplysia nervous system proteins, including those of the bag cell neurons.In cell-free preparations of Aplysia CNS, we demonstrated Ca/CaM-stimulated protein phosphorylation that co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
27
1

Year Published

1987
1987
1998
1998

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(33 citation statements)
references
References 35 publications
5
27
1
Order By: Relevance
“…Few detailed kinetic and substrate specificity studies have been reported comparing mammalian CaM-PK I1s to each other (32) and none has been reported comparing mammalian CaM-PK Hs to those from nonmammalian sources. DeRiemer et al reported rates of phosphorylation of synapsin I and MAP-2 of 0.89 and 0.04 nmol per min per mg of Aplysia CaM-PK II, respectively (41), which are far below those reported here for ACMPK. The isolation of a fungal multifunction Ca2+ /CaM-dependent protein kinase capable of recognizing mammalian protein substrates and being regulated by mammalian CaM indicates a high degree of functional conservation among CaM-dependent multifunctional protein kinases in eukaryotic organisms.…”
Section: Resultscontrasting
confidence: 70%
See 1 more Smart Citation
“…Few detailed kinetic and substrate specificity studies have been reported comparing mammalian CaM-PK I1s to each other (32) and none has been reported comparing mammalian CaM-PK Hs to those from nonmammalian sources. DeRiemer et al reported rates of phosphorylation of synapsin I and MAP-2 of 0.89 and 0.04 nmol per min per mg of Aplysia CaM-PK II, respectively (41), which are far below those reported here for ACMPK. The isolation of a fungal multifunction Ca2+ /CaM-dependent protein kinase capable of recognizing mammalian protein substrates and being regulated by mammalian CaM indicates a high degree of functional conservation among CaM-dependent multifunctional protein kinases in eukaryotic organisms.…”
Section: Resultscontrasting
confidence: 70%
“…Multifunctional CaM-PK Ils have been isolated from mammalian brain (3,4), liver(5), pancreas (37), and skeletal muscle (38) as well as the nonmammalian tissues Torpedo electric organ (6), Aplysia neurons (7), and sea urchin egg (39). Cross-reactivity between antibodies to rat brain CaM-PK II and CaM-PK Ils from rabbit skeletal muscle (40) and Aplysia californica (41) have been reported.…”
Section: Resultsmentioning
confidence: 99%
“…Further study is n e e d e d to precisely define the time course of the change in expression of CaM mRNA, as well as the time course of expression for the other mRNAs. CaM can influence a variety of cell functions (for review, see Means 1988;Means et al 1991;Bachs et al 1994;Gnegy 1995), and numerous CaM-regulated enzymes have b e e n found in Aplysia neurons (Novak-Hofer and Levitan 1983;Saitoh andSchwartz 1983, 1985;DeRiemer et al 1984;Kramer et al 1988;Eliot et al 1989;Abrams et al 1991;Endo et al 1992;K.A. Ocorr and J.H.…”
Section: Cammentioning
confidence: 99%
“…Studies from a number of laboratories have demonstrated that isoenzymes of CaM-kinase II are also present in most mammalian tissues examined. Indeed, the kinase has been highly purified from mammalian brain [7,[10][11][12][13][14], liver [8,15,16], skeletal muscle [17], heart [18], pancreas [19], retina [20], lung [21], parathyroid [22], mammary gland [23] and intestinal brush border [24], as well as neural tissues of Aplysia [25], electric eel [26], squid [27] and Drosophila [28]. The isoenzymes are characterized by a large native molecular mass (300-700 kDa), subunits in the range 50-62 kDa, and similar or identical catalytic properties against several protein substrates (references listed above and [29]).…”
Section: Species Tissue and Subcellular Distributionmentioning
confidence: 99%